Role of Catalase Enzyme in the Existence of Allicin on Hep-G2 Cell Line - Karimi, Bashir Ahmad; Ahmadyfalah, Sayed Abdul Aziz; Shariati, Abdulrahim (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
In recent years, there has been significant attention on the use of chemical and bioactive compounds extracted from medicinal plant sources to prevent and treat various diseases. Among the active components of herbal medicines, curcumin, resveratrol, quercetin, emodin, silybin, and their derivatives have been particularly discussed in the treatment of chronic and common disorders such as cardiovascular, metabolic, neurogenic diseases, and cancer. It is estimated that about sixty percent of currently widely used anticancer drugs are derived from natural sources. These compounds also play an important role in cancer prevention, due to their high ability to scavenge free radicals, inhibit cell growth, and induce apoptosis. For centuries, garlic and its derived compounds have attracted researchers' attention due to their health-promoting effects. Various bioactive compounds in garlic are responsible for its health benefits, among which allicin is one of the key components. Allicin is responsible for the pungent odor of garlic and is one of the most important organosulfur compounds in garlic, making up about 70% of the thiosulfate compounds. Allicin is produced during the crushing of garlic through the enzymatic activity of alliinase on alliin and is effective against a wide range of microorganisms. The antimicrobial and antioxidant properties of allicin are attributed to its reaction with the thiol groups of various enzymes. Allicin prevents cancer onset and progression by blocking metastasis and inhibiting excessive cell proliferation. This study investigates the role of the enzyme catalase in the presence of allicin on the Hep-G2 cell line. Allicin, the active ingredient in garlic, was applied in its pure form to Hep-G2 cancer cells in a concentration range from 0 to 250 µg/mL for 24 hours. The MTT assay revealed that allicin had an inhibitory effect on the proliferation of these cells. A proposed mechanism for the cytotoxic effect of allicin is the impact of oxygen free radicals on the biochemical structure of these cells. The general reduction in catalase enzyme activity leads to an increase in these free radicals. Ultimately, by inducing oxidative stress and decreasing catalase activity, allicin causes cellular toxicity and exhibits anticancer properties on Hep-G2 cells.